2010
DOI: 10.1017/s1833367200002005
|View full text |Cite
|
Sign up to set email alerts
|

Does fun work? The complexity of promoting fun at work

Abstract: For some years now there has been growing enthusiasm amongst practitioners, managers and some academics about the value of promoting fun at work, resulting in a substantial body of managerial literature. As a result, the authors believe that fun at work deserves further research attention. In this paper the authors critically review the large body of practitioner and management literature promoting fun at work. We find this literature dependent on a number of untheorised, untested assumptions about the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…A growing body of literature has investigated workplace fun (Owler, Morrison, & Plester, 2010; Plester & Hutchison, 2016), with most authors seeking to describe managerial attempts to create and utilise ‘social’ fun at work to influence worker engagement and productivity (e.g., Becker & Tews, 2016; Fine & Corte, 2017; Fluegge-Woolf, 2014). Few authors have examined the investment by individuals, or the strategic attempts that individuals make, to create and sustain an experience of fun for themselves (Owler & Morrison, 2012; Plester, Cooper-Thomas, & Winquist, 2015).…”
Section: Background and Research Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has investigated workplace fun (Owler, Morrison, & Plester, 2010; Plester & Hutchison, 2016), with most authors seeking to describe managerial attempts to create and utilise ‘social’ fun at work to influence worker engagement and productivity (e.g., Becker & Tews, 2016; Fine & Corte, 2017; Fluegge-Woolf, 2014). Few authors have examined the investment by individuals, or the strategic attempts that individuals make, to create and sustain an experience of fun for themselves (Owler & Morrison, 2012; Plester, Cooper-Thomas, & Winquist, 2015).…”
Section: Background and Research Focusmentioning
confidence: 99%
“…On the other hand, the initiatives may not suit the workers or place pressure on them to act in a certain way. For instance, workers may not respond well if they feel that management is placing a higher priority on fun than other more important aspects of worker wellbeing or productivity (Baptiste, 2009; Fleming, 2005; Owler, Morrison, & Plester, 2010; Warren & Fineman, 2007). Clancy and Linehan (2019) found that workers were more amenable to management-led fun initiatives if they perceived that they were implemented for their benefit, rather than the organisation's benefit.…”
Section: Background and Research Focusmentioning
confidence: 99%
“…These heterogeneous definitions make it difficult to determine what fun is, but they do depict the many different uses of fun in the literature which are a result of the many activities and behaviours that can be considered fun. The definitions are limited to presenting a few activities and behaviours, which reflect the problems inherent in trying to find a comprehensive definition, as what is fun is both subjective and context related (Owler et al 2010). In the literature, three main clusters of fun activities and behaviours have already been identified helping researchers to better understand and operationalize the concept of fun; managed (fun activities initiated or supported by the organization), organic (activities that the employees engage in by themselves), and task related, but, little has been done so far to clearly distinguish among them (Plester et al 2015).…”
Section: What Is Fun?mentioning
confidence: 99%
“…The organizational culture itself seems to play an important role. Owler et al (2010) based on Schein's framework for understanding organizational culture described how espoused values (second level) like fun at work might not reflect the underlying assumptions and values that exist at a deeper organizational level (third level) and thus cause contradictions, incongruities and dissonance. The probability of controlled fun resulting in negative outcomes is possible when they do not reflect the values of the organization or when management is not perceived as benevolent.…”
Section: Trustmentioning
confidence: 99%
“…These heterogeneous definitions make it difficult to determine what fun is, but they do depict the many different uses of fun in the literature which are a result of the many activities and behaviours that can be considered fun. The definitions are limited to presenting a few activities and behaviours, which reflect the problems inherent in trying to find a comprehensive definition, as what is fun is both subjective and context related (Owler, Morrison, & Plester, 2010). In the literature, three main clusters of fun activities and behaviours have already been identified helping researchers to better understand and operationalize the concept of fun; managed fun (fun activities initiated or supported by the organization), organic fun (activities that the employees engage to by themselves), and task related fun, but, little has been done so far to clearly distinguish among them (Plester et al 2015).…”
Section: A Modern Psychological Conceptmentioning
confidence: 99%